Assessment of meteorological variables and heat fluxes from atmospheric reanalysis and objective analysis products over the Bering Sea. (29th April 2019) - Kong, Bin; Liu, Na; Lin, Lina; He, Yan; Wang, Yingjie; Pan, Zengdi
Abstract: Surface meteorological variables and heat fluxes in the Bering Sea obtained from Chinese Arctic buoys and U.S. National Data Buoy Center buoys are compared with seven products. The seven products comprise six reanalysis products, that is, the European Centre for Medium‐Range Weather Forecasts Interim Reanalysis (ERA‐Interim), Japanese 55‐year Reanalysis (JRA‐55), Modern Era Retrospective‐analysis for Research and Applications Version 2 (MERRA2), National Center for Environmental Prediction‐National Center for Atmospheric Research Reanalysis 1 (NCEP1), the National Centers for Environmental Prediction‐Department of Energy Reanalysis 2 (NCEP2), and Arctic System Reanalysis Version 2 (ASR2), and one objective analysis product, that is, Objectively Analyzed Air‐Sea Fluxes (OAFlux). The best estimates of the air temperature and specific humidity is obtained by JRA‐55, of the sea surface temperature by ERA‐Interim, MERRA2, and ASR2, and of the wind speed by ERA‐Interim. Shortwave radiation is overestimated by all of the products. Longwave radiation is significantly underestimated by all of the products except for ASR2 in the Bering Sea. In terms of the turbulent heat fluxes, the products can be divided into two classes. ERA‐Interim, JRA‐55, MERRA2, and ASR2 obtain better estimates of the latent heat flux (LHF) and sensible heat flux (SHF) compared with NCEP1, NCEP2, and OAFlux. We investigate two possible causes of the discrepancy in the turbulent heat fluxes obtained by the buoy and reanalysis products, that is, the bulk algorithm and meteorological variables. The algorithm is not the dominant cause of the discrepancy between the turbulent heat fluxes obtained by the buoy and reanalysis products in the Bering Sea. Among the meteorological variables, the difference in specific humidity contributes the largest root‐mean‐square error (RMSE) of LHF between buoy and all reanalysis products, and the difference in air temperature contributes the largest RMSE of SHF. Abstract : The recalculated flux which is calculated by COARE 3.5 (the same algorithm with buoy flux) with the meteorological variables obtained from reanalysis products does not reduce the discrepancy with the buoy flux when comparing with the reanalysis products flux. Therefore, the algorithms are not the main cause of the differences in the turbulent heat fluxes obtained from the buoy data and the reanalysis products in the Bering Sea.